Smart door access system with AI security and IoT application - Lee, Kar Tien (2023)

(untitled)
Due to the advancement of technology, the traditional way to open a lock or enter a building has been replaced by a smart door access system. The smart door access system is a digital technology that allows users to replace their troublesome key with some credentials, for example, RFID cards, smart tags, mobile applications, face, fingerprint or voice. The system provides the user a faster, safer, and more convenient way to access the lock. This project has created a smart door access system with hardware and software. The access system of this project contains one central control unit, a reader unit, a camera unit, an internal switch, a door sensor, and a solenoid lock with a driver. The Blynk IoT platform works as the software for the system. The system supports three access methods, which are the double-factor authentication method (scan a RFID card and key in password), Blynk mobile application method (press unlock button), and the internal switch method (press the limit switch). If the wrong card ID or wrong password is provided to the system twice, a notification is received on the Blynk mobile application, and the camera unit is activated to capture an image. The image will be stored as evidence in the receiver's email after receiving it. In order to let the user control the system over a long distance, the Blynk application has been used as a mobile application in the smartphone. This mobile application can download directly from Google Play Store or Apple Store. The internet is a connection between the application and the system. An overall system analysis has been performed to determine the system's functionality and reliability. The system analysis is divided into five parts, and the accuracy for each is calculated. Project cost analysis has also been done to determine the spending amount for the whole system. The total cost to build the whole project is RM257.67, but the actual cost for the system is only RM170.47. The weakness of the project is pointed out in the last chapter, and the ways to improve the weakness are recommended in the same chapter